Impacts of subclinical hypocalcemia on physiological, metabolic, and productive responses of Holstein × Gir dairy cows - Rodrigues, Rodrigo [UNESP]; Cooke, Reinaldo F; Ferreira, Hingryd A. O [UNESP]; Florido, Renato R [UNESP]; Camargo, Victoria [UNESP]; De Godoy, Hirys O [UNESP]; Bruni, Giulia A [UNESP]; Vasconcelos, José L. M [UNESP] (Oxford University Press (OUP), 2019)
This study compared physiological and productive parameters in Holstein × Gir dairy cows diagnosed or not with subclinical hypocalcemia (SCH) during early lactation. Nonlactating, multiparous cows (n = 32) were enrolled in this experiment 21 d prior to expected date of calving. Cows were maintained in a single pen with ad libitum access to corn silage before calving and received a limit-fed prepartum concentrate. Cow body weight (BW) and body condition score (BCS) were recorded weekly, and blood samples were collected on days-21,-14,-9,-6, and-3 relative to expected calving. After calving (day 0), cows were managed in a single pen with ad libitum access to a total mixed ration, and were milked twice daily. Cow BW and BCS were recorded upon calving and then weekly. Milk production was recorded daily and milk samples collected weekly until 30 d in milk (DIM). Blood was collected during the first 5 DIM, and at 6, 9, 16, 23, and 30 DIM. Cows were classified with SCH when mean total serum Ca during the first 5 DIM was ≤2.125 mmol/L. Cows diagnosed with SCH (n = 11) had less (P ≤ 0.04) mean BCS (2.85 vs. 3.07; SEM = 0.07) and less concentrations of serum insulin (0.396 vs. 0.738 ppmol/L; SEM = 0.115) and insulin-like growth factor I (35.9 vs. 57.9 ng/mL; SEM = 4.2), and these outcomes were noted since 21 d prior to expected calving. Cows diagnosed with SCH had greater (P < 0.01) serum concentrations of cortisol at calving (30.2 vs. 22.4 ng/mL; SEM = 2.0), serum haptoglobin at 3 and 6 DIM (0.453 vs. 0.280 mg/mL on day 3 and 0.352 vs. 0.142 mg/mL on day 6; SEM = 0.046), and tended (P = 0.09) to have greater mean concentrations of nonesterified fatty acids from calving to 30 DIM (0.368 vs. 0.304 μEq/L; SEM = 0.026). No differences were detected (P ≥ 0.41) for cow BW and milk production. Cows diagnosed with SCH had less (P = 0.05) mean concentrations of milk total solids (13.2 vs. 13.8 %; SEM = 0.21), tended to have less (P ≤ 0.10) mean concentrations of milk fat (4.34 vs. 4.81 %; SEM = 0.20), protein (3.31 vs. 3.45 %; SEM = 0.05), and lactose (4.45 vs. 4.55 %; SEM = 0.04), and had greater (P = 0.02) milk somatic cell count during the initial 14 DIM (504 vs. 140 cells/μL; SEM = 90). Collectively, Holstein × Gir cows diagnosed with SCH upon calving had altered periparturient physiological parameters denoting reduced energy nutritional, increased milk somatic cell count, and less concentration of milk components during early lactation compared with normocalcemic cows.
Keywords: Holstein × Gir cows; metabolism; milk production; subclinical hypocalcemia